PENGARUH PENAMBAHAN KOMBINASI LEVAMOSIL DAN VAKSIN Aeromonas hydrophila TERHADAP PERTUMBUHAN, JUMLAH NEUTROFIL, DAN SINTASAN IKAN GURAMI (Osphronemus gouramy Lac.) - Purbomartono, Cahyono; Mulia, Dini Siswani (Universitas Muhammadiyah Purwokerto, 2009)
The research conducted n gouramy fish with size among 12-15 cm in length and average of 30 g in wight. the treatment used levamisol and their combination with vaccine Aeromonas hydrophila which applied by immersion during 6 hours. Methods of research used experimentally laboratories using completely randomized design with 6 replication. The fishes placed in aquaria, each of its 12 fishes. The dataâs observed consisted of growth both of length and weight, number of neutrophyl, survival rate, and water quality. The aim of the research was to know the effect of levamisol and its combination with vaccine on the respons against their growth, neutrophyl responses and survival rate of gouramy fishes. The results showed, treatment of levamisol and their combination with vaccine could increase on the growth and the best result revealed on P1, as 1.2 cm and 0.68 g for their length and weight respectively. Cellular response of neutrophyl showed better reached at P3 and P4 as number of 5.3 neutrophyl cell between on day H18 and H24. Higher survival rate reached on P2 and P3. During researched, water quality was on qualified standard requirements for larvae rearing.